METHODOLOGICAL ASPECTS OF CREATING AND USING AN ELECTRONIC TEXTBOOK OF POLYMER CHEMISTRY - Khaydarova Charos Kasimovna (Scholar Express Journal, 2024)
In the article, teaching based on 3D technologies, Augment realityAugment reality (AR), Virtual reality Virtual reality (VR), Mixed reality Mixed reality (MR), programs focused on effectiveness in teaching chemistry.
Keywords: virtual education; Augment reality; Virtual reality Virtual reality